Operation of paddy field tillage wheel based on SPH - Zheng, Xian; Yang, Hongyan; Yang, Wang (International Journal of Agricultural and Biological Engineering, 2024)
A new type of paddy field micro-tiller that places the rotary cutter roller in front of the driving wheel has been developed in China. Its driving wheel not only has a driving function, but also has the function of crushing and stirring the soil, so it is called a tillage wheel. However, at present, there are few studies on the wheel’s operating mechanism and force and the influences of factors on the wheel’s operational performance, which is not conducive to its optimal design. This study verifies the rationality of the soil-tillage wheel system modeling method based on the smoothed particle hydrodynamics method (SPH) through field test. The movement track and force variation of the single-wheel blade in soil as well as the interaction between the single-wheel blade and soil were studied using the established simulation model. Moreover, mathematical models were developed to examine how various factors affect the wheel’s operational performance. The results show that the modeling method is reasonable. As the rotation angle of the wheel blade increases, both the horizontal thrust and support force initially rise and then fall. The maximum horizontal thrust at the slip rate of 3.1% is 42.28% smaller than that of 26%. But the maximum support force at the slip rate of 3.1% is 10% greater than that of 26%. When the outer diameter of the wheel, the number of wheel blades, and the inclination angle of the wheel blade are small, as the wheel blade angle increases, the average advance speed increases, and the stirring degree decreases, and vice versa. Using the simulation method to study the wheel’s operating mechanism and force and the influences of various factors on the wheel’s operational performance is of great significance to the optimization of its design. Keywords: tillage wheel, single-wheel blade, numerical simulation, operating mechanism, mathematical model, factor influence DOI: 10.25165/j.ijabe.20241706.8908 Citation: Zheng X, Yang H Y, Yang W. Operation of paddy field tillage wheel based on SPH. Int J Agric & Biol Eng, 2024;17(6): 176–184.